PENGARUH BAHASA PERTAMA TERHADAP BAHASA KEDUA DALAM KARANGAN SISWA KELAS V SD - Hastuti, Hastuti (Mimbar Sekolah Dasar, 2015)
The purpose of this research is to determine and describe the influence of first language to the second language contained in essay fourth-grade students of SD Muhammadiyah 1 Bandar Lampung. The method used is a descriptive method. Data analysis technique that is used is composed test data analysis to determine the level of use under the influence of the first language to the second language in an essay fourth-grade students of SD Muhammadiyah 1 Bandar Lampung The populations in this study were all fourth-grade students of SD Muhammadiyah 1 Bandar Lampung totaling 25 students. Sample of this research is sample population. In the concocted test data analysis fourth-grade students of SD Muhammadiyah 1 Bandar Lampung there is the influence of first language in the essay by 55.05%. This means that the influence of Lampung language in a fourth-grade student essay Muhammadiyah 1 Bandar Lampung, Lampung language otherwise low.Keywords: the influence of first language, second language, an essay the students.